2022
DOI: 10.3390/ph15040440
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag as an Allosteric Inhibitor of the METTL3-14 Complex Affecting the m6A Methylation of RNA in Acute Myeloid Leukemia Cells

Abstract: N6A-methyladenosine (m6A) post-transcriptional modification, the most abundant internal RNA modification, is catalyzed by the METTL3-14 methyltransferase complex. Recently, attention has been drawn to the METTL3-14 complex regarding its significant roles in the pathogenesis of acute myeloid leukemia (AML), attracting the potential of novel therapeutic targets for the disease. Herein, we report the identification and characterization of eltrombopag as a selective allosteric inhibitor of the METTL3-14 complex. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…More recently, Yankova et al, have identified a selective METTL3 catalytic inhibitor, STM2457, which could suppress the growth of AML [163]. Lee et al, reported that eltrombopag selectively inhibits the catalytic form of the METTL3-14 complex that can decrease the m 6 A modification on RNA in AML cells [164]. Meanwhile, two FTO inhibitors (FB23 and FB23-2) have been designed by Huang et al, exhibiting a selective inhibitory effect on the proliferation of AML [165].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yankova et al, have identified a selective METTL3 catalytic inhibitor, STM2457, which could suppress the growth of AML [163]. Lee et al, reported that eltrombopag selectively inhibits the catalytic form of the METTL3-14 complex that can decrease the m 6 A modification on RNA in AML cells [164]. Meanwhile, two FTO inhibitors (FB23 and FB23-2) have been designed by Huang et al, exhibiting a selective inhibitory effect on the proliferation of AML [165].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 11a forms extensive van der Waals interactions with aromatic residues and hydrophobic amino acids such as Val452, Val485, and Val487. 145 The importance of the carboxylic acid for the METTL3−11a interaction was confirmed by the massive drop in inhibitory potency caused by the removal or esterification of the carboxylic acid (compound 11b or 11c, respectively). Similarly, the removal of the phenolic hydroxyl (11d) group caused a fourfold decrease in potency (Figure 7B).…”
Section: ■ Mettl3 Small-molecule Inhibitorsmentioning
confidence: 98%
“…According to docking studies, 11a binds to an allosteric binding site distinct from the SAM pocket, with the carboxylic acid moiety forming hydrogen bonds with the backbone amides of Asp499 and Cys550, while the phenol forms a hydrogen bond with the carboxylate group of Asp453 and the hydrazine moiety forms a hydrogen bond with the carboxamide group of Gln496. Moreover, 11a forms extensive van der Waals interactions with aromatic residues and hydrophobic amino acids such as Val452, Val485, and Val487 . The importance of the carboxylic acid for the METTL3– 11a interaction was confirmed by the massive drop in inhibitory potency caused by the removal or esterification of the carboxylic acid (compound 11b or 11c , respectively).…”
Section: Mettl3 Small-molecule Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations